Behavior of RBS Beams Reinforced by Stiffeners Subjected to Cyclic Loading - Iori Kanao; Tianrui He; Zheng Yu; Kiyotaka Morisako (Journal of Engineering)
This paper presents a numerical study of reduced beam section (RBS) beams with vertical and horizontal stiffeners. For RBS beams, it is speculated that strength deterioration will be caused by lateral buckling and local buckling. Supplemental lateral bracing (SLB) can prevent lateral buckling but not prevent local buckling in the RBS portion. In the previous research, the effect of vertical or horizontal stiffeners in RBS portion was shown to restrain local buckling of the RBS portion. But RBS with vertical stiffeners causes stress concentration at flange, and strength of RBS with horizontal stiffeners is lower than RBS with vertical stiffeners. In this paper, various patterns of placing stiffeners at the RBS portion are presented. The effect of vertical stiffeners and horizontal stiffeners arranged at the RBS portion is discussed based on length. It is confirmed that, without placing supplemental lateral bracing (SLB), vertical and horizontal stiffeners can delay the occurrence of local buckling and prevent stress concentration. Moreover, the strength can be sustained above 0.8Mp.